HLA prevalence in Iraqi patients with ischemic heart disease. - AL-Dileamy, Basil N.; AL-Obeidy, Eman Sh. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: The etiology of ischemic heart disease (IHD) is believed to have an immunological component. Association with human leukocyte antigens (HLAs) has been previously reported, particularly with DR6.Patients and methods: 75 cardiac patients were admitted to the coronary care unit, Baghdad Teaching Hospital over the period October 2008-May 2009 with the clinical diagnosis of acutecoronary syndrome and STEMI myocardial infarction their ages range was (25-82) years the number of male was (55) (73.3%) and female was (20) (26.7%). All cases have routine ECG, cardiac marker’s measurements, routine haematological, Biochemical test and 2mls of blood reserved for HLA study.Results: It was found that HLA-DR1 (8%) (P 0.001) has significant risk factor in the development of ischemic heart disease while HLA B (62%) (P 0.0009) has a protection factor in ischemic heart disease.Conclusions: Our result suggests that strong relation between the incidence of acute ischemic episode (acute coronary syndrome and STEMS myocardial infarction and HLA-DR1) which mean that there may be predisposing genetic factor for the development ischemic heart disease.